Crystallisation of non-stoichiometric cordierite glasses - Azín, N.J. (2005)
The crystallisation of a cordierite non-stoichiometric glass (25 wt.% Al2O3, 63 wt.% SiO2 and 12 wt.% MgO) located in the cordierite crystallisation field in the Al2O3·SiO2·MgO system was studied. Glass fragments were obtained by quenching the melt in cold water. Two granulometric fractions, fine (51.8 wt.% < 37 μm) and coarse (D50 = 239 μm), were prepared by crushing, dry milling and/or sieving. A great tendency to devitrify and a high glass transition temperature (Tg = 830 °C) were determined. Temperatures between 940 and 1300 °C and times up to 24 h were selected in order to crystallise the glass. The crystallisation was followed by differential thermal analysis (DTA), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Three exothermic peaks between 970 and 1180 °C assigned to μ- and α-cordierite crystallisations with different overlapping degrees depending on both the glass particle size and the heating rate were registered by DTA. No difference was established with respect to the crystallisation mechanism of stoichiometric cordierite glass. However, it was possible to differ the temperature of crystallisation of α-cordierite from both surface and bulk mechanisms. Three non-isothermal methods were used to estimate the activation energy to μ-cordierite crystallisation from both glass granulometric fractions.